Incorporation of Human Factors in Risk Analysis of Oil and Gas Pipeline Using Bayesian Network - Alaw, Fares Ahmed; Nurul Sa'aadah, Sulaiman; Tan, Hendry (Universiti Malaysia Pahang, 2018)
Billions of barrel of oil and gas are consumed around the world daily and these oil and gas are being mainly transported and distributed through pipelines.